2014
DOI: 10.1159/000364849
|View full text |Cite
|
Sign up to set email alerts
|

Management of Young Blood Donors

Abstract: The emphasis on high-school blood drives and acceptance of 16-year-old blood donors led to more research on physiologic and psychological ways to decrease vasovagal reaction rates in young blood donors and to increase donor retention. Research on how to accomplish this has been advantageous for the blood collection industry and blood donors. This review discussed the current situation and what can be done psychologically, physiologically, and via process improvements to decrease vasovagal reaction rates and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 87 publications
3
32
2
Order By: Relevance
“…The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
Section: Discussioncontrasting
confidence: 58%
“…The additional analysis that included more patients (the overall group) revealed that lower systolic blood pressure was the strongest independent predictor of VVR (OR = 2.45 (95% CI = 1.50-4.01), p < 0.001)). Our data add evidence that patients with a lower blood pressure are more susceptible to VVRs.The high risk groups for VVRs are generally reported to be young, female, first-time donors [2,18,[25][26][27]. In our analysis, female gender was a significant risk factor in the univariate analysis in group I; however, it was not significant in the multivariate analysis in both group I and the overall group.…”
contrasting
confidence: 58%
“…While future research should evaluate this proposed trajectory through tracking a cohort of first‐time donors through conversion to (potential) negative events during and after plasmapheresis, it also suggests attention should be focused on early career donors who are converted. Although a range of successful interventions have been developed for vasovagal reactions in WB donors, there are few interventions for reactions to plasmapheresis. The mid‐donation infusion of saline used in Australia (http://www.blood.gov.au/pubs/2013-haemovigilance/section7.html) may not be acceptable to all due to the hemodilution of plasma proteins that occurs with this infusion .…”
Section: Discussionmentioning
confidence: 99%
“…It also allowed blood banks to build enough stock of blood products to fulfill their obligations to acute emergencies as well as supportive therapy for hematology/oncology patients and surgical operations, including open heart surgery and, more recently, transplant surgery including bone marrow transplant in some main hospitals. Second, it helped in laying the bases for potential future “voluntary” blood donations, particularly first‐time donors, who, in this system of involuntary blood donation, are forced to overcome the “fear barrier.” Table gives a timeline for the key developments in the blood donor services in the KSA (Table ).…”
Section: The Emergence Of the Blood Donor System In The Ksamentioning
confidence: 99%